An evaluation of the emergency care training workshops in the province of KwaZulu-Natal, South Africa - Mergan Naidoo (AOSIS, 2017)
Background: Emergency care in South Africa is both complex and complicated which is further compromised by inadequately trained healthcare workers. Academic disciplines at the University of KwaZulu-Natal have run emergency care workshops for doctors and nurses providing primary emergency care, in the province for the last 14 years. This delivery of such training has evolved over time. Objectives: The aim of this study was to evaluate the feedback and knowledge of participants attending the last nine workshops. Methods: An evaluation questionnaire asked participants to assess the workshops held in the province and to rate their perceived improvement in knowledge. A multiple choice questionnaire was conducted in the last few workshops and was administered pre- and postworkshop. The data were extracted onto an Excel spreadsheet and analysed in Stata version 13. Outcome measures were generated using percentages. A paired t-test was used to compare knowledge scores. Open-ended questions were also used to identify areas for future improvement. Results: The majority (89.4%) of the participants worked in the primary emergency care setting. All participants found the quality of training, the facilitators and the training material good or excellent. Participants' perceived improvement in knowledge and skills and the objective measure of knowledge improved significantly (p < 0.001). Conclusion: Emergency care education using a combination of inter-professional simulation and lecture-based teaching has the potential of contributing towards better educational outputs in both undergraduate and postgraduate curricula.